The Impact of Workload and Workplace Conditions on Worker Performance at Pharmacy Industry - Nur Tyastuti Puntorini; Syamsul Hadi; Kusuma Chandra Kirana (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - Pharmaceutical services in hospitals are essential for ensuring healthcare quality; however, the effectiveness of pharmacy staff is frequently compromised by excessive workloads and inadequate work environments. Previous research has investigated these factors individually; however, the collective influence on employee performance is still a subject of discussion. This study analyzes the impact of workload and work environment on employee performance in the Pharmacy Unit, thereby addressing a gap in the current literature. Design/methodology/approach - Primary data was collected from 173 pharmacy employees using a census sampling technique via online surveys. Multiple linear regression analysis was utilized to evaluate the hypotheses. Originality -  This study contributes to the literature by examining the combined effect of workload and work environment on performance—an area that has previously been studied in isolation. Recommended strategies include equitable task distribution, stress management programs, and workspace enhancements to sustain employee productivity. Findings and Discussion - The findings demonstrate that workload adversely affects performance, whereas a supportive work environment enhances performance. Workload alone does not consistently lead to reduced performance; rather, its detrimental effects are pronounced when coupled with inadequate work conditions. Performance may deteriorate when employees encounter excessive workloads without sufficient environmental support. Conclusion - The findings indicate that hospital management ought to prioritize the optimization of workload and enhancements in the workplace to improve the quality of pharmaceutical services.